2005
DOI: 10.1371/journal.pmed.0020204
|View full text |Cite|
|
Sign up to set email alerts
|

Estimation of the Total Parasite Biomass in Acute Falciparum Malaria from Plasma PfHRP2

Abstract: BackgroundIn falciparum malaria sequestration of erythrocytes containing mature forms of Plasmodium falciparum in the microvasculature of vital organs is central to pathology, but quantitation of this hidden sequestered parasite load in vivo has not previously been possible. The peripheral blood parasite count measures only the circulating, relatively non-pathogenic parasite numbers. P. falciparum releases a specific histidine-rich protein (PfHRP2) into plasma. Quantitative measurement of plasma PfHRP2 concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
441
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(467 citation statements)
references
References 19 publications
19
441
4
3
Order By: Relevance
“…The difficulty in estimating the number of parasites sequestered in tissues has long hampered clinical investigations of malaria, because it is these parasites that are thought to be critical for disease pathogenesis. 39,40 Our data show that Treg depletion results in a major reduction in tissue parasites that may explain why these animals fail to develop ECM.…”
Section: Discussionmentioning
confidence: 80%
“…The difficulty in estimating the number of parasites sequestered in tissues has long hampered clinical investigations of malaria, because it is these parasites that are thought to be critical for disease pathogenesis. 39,40 Our data show that Treg depletion results in a major reduction in tissue parasites that may explain why these animals fail to develop ECM.…”
Section: Discussionmentioning
confidence: 80%
“…Un método más apropiado parece ser la estimación de la biomasa parasitaria, la cual se ha asociado con la gravedad de la enfermedad, al contrario que la parasitemia periférica (40). No se utiliza en la práctica un criterio de hiperparasitemia en las infecciones por P. vivax, posiblemente porque la enfermedad producida por esta especie se ha considerado más benigna.…”
Section: Signos Asociados Con Complicación En El Análisis Bivariadounclassified
“…According to the TFM, sequestration and/or sequestration-related events is (are) crucial step(s) leading to disease pathogenesis primarily because it is associated with EC activation 8-10, endothelium TF expression, and initiation of the coagulation cascade. Strong support for sequestration in disease pathogenesis comes from IHC and pathology studies performed in African and Asian patients 5 -10, from studies that demonstrated a correlation between sequestration and disease severity using an indirect marker of sequestration 6 , from clinical trials that used artesunate, which targets young and mature forms of the parasite 35 , and from hemoglobinopathies (e.g., hemoglobinopathy C) that protect P. falciparum-infected and (presumably) sequestration-free patients from severe disease 36 ; however, it is clear that sequestration per se does not account for severe disease, as it is also found in uncomplicated cases [1][2][3] .…”
Section: The Tissue Factor Model For Malaria Pathogenesismentioning
confidence: 99%